(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the adherence to hypertension treatment among outpatients and related factors at the Senior Officer Clinic, 108 Central Military Hospital. Subjects and methods: A cross-sectional descriptive study of 255 patients diagnosed with hypertension, undergoing treatment and follow-up at the Senior Officer Clinic from March to June 2024. Results: The study population was predominantly male (95.3%) with an average age of 68.77 ± 9.09 years. The 60-69 age group was the largest, accounting for 39.6%. Patients with a history of hypertension longer than 10 years made up 51.8%. Those taking one antihypertensive drugs comprised 81.2%. The most common comorbidities were lipid metabolism disorders (59.22%) and diabetes (40.78%). Medication adherence was good in 92.9% of patients. Among the 7 characteristics studied, there were marital status, age group, and the number of medications being taken significantly influenced medication adherence (p < 0.05). Conclusion: Patients treated and managed for hypertension at the Senior Officer Clinic had a high average age (68.77 ± 9.09 years). Dyslipidemia and diabetes were the two common comorbidities. Most patients showed good adherence to their treatment regimen (92.9%). There was an association between marital status, age group, and the number of medications being taken with adherence to hypertension treatment.